Technical basics and results of the prosthetics original repair of large incisional hernias - Adolfo Rafael Jaén Oropeza; José Miguel Gonzalo Goderich Lalán; Elvis Pardo Olivares; Miguel Ángel Quevedo Tamayo; Ernesto Casamayor Callejas (Centro Provincial de Información de Ciencias Médicas, 2017)
Introduction: the large incisional hernia has a high recurrence in spite of the use of meshes.   Objective: to describe a technique for the repair of the abdominal wall defects of more than 15-20 cm in diameter.   Methods: a descriptive, quantitative, retrospective - prospective and longitudinal study of 62 patients operated by means of this technique was carried out in the "Dr. Juan Bruno Zayas Alfonso"UniversityGeneralHospital inSantiago de Cuba, from 2003  to 2015.  Results: there was a prevalence of the female sex, 45-65 years age group, hypertension as comorbidity with previous gynecological abdominal surgery, infraumbilical localization of the hernial site, Bendavid hernioplasty and abdominoplasty as associated surgery.  The endotraqueal general anesthetic as anesthetic method had a higher incidence, the most outstanding postoperative complication was the serous complication; there was neither mortality, nor recurrences.   Conclusions: this is a safe and effective method for the repair of large hernial defects of the front abdominal wall.